Integrating Theological Knowledge, Attitudes, and Life Meaning in Christian Education: A Literature Review on Spiritual Maturity - Ditakristi, Agiana Her Visnhu (LP. Ma'arif Janggan Magetan, 2024)
This study addresses the persistent problem in Christian education where theological instruction remains predominantly cognitive, resulting in a gap between theological knowledge and authentic spiritual practice. The purpose of this research is to analyze and synthesize the relationship among theological knowledge, faith attitude, and meaning of life in shaping spiritual maturity. Using an integrative literature review approach, the study systematically examined 45 selected articles from major databases such as Scopus, ProQuest, and SpringerLink. The findings reveal that spiritual maturity emerges from the synergistic interaction of three dimensions: theological knowledge as the cognitive foundation, faith attitude as the affective internalization, and meaning of life as the existential bridge that connects belief with spiritual experience. This integration forms a new conceptual model that emphasizes reflection, personal meaning, and transformation as the essence of Christian education. The novelty of this study lies in the formulation of a comprehensive framework linking cognition, affection, and existential meaning in one unified model of spiritual maturity—an approach rarely developed in the Indonesian context. The study concludes that effective Christian education must unite head, heart, and hands through reflective and transformative learning processes. Practically, the results contribute to curriculum development in Christian education that balances theological understanding with personal and spiritual formation.